Analisis Pengendalian Kualitas Produk Base Plate Kereta Api Dengan Menggunakan Metode Seven Tools Di PT Sinar Semesta - Ahmad Sobirin; Ari Zaqi Al Faritsy (Politeknik Kampar, 2024)
PT Sinar Semesta is an industrial company engaged in metal casting, one of which is Base Plate which is located on Jl. Raya Solo-Yogya Km. 26 Klepu, Ceper, Klaten. The problem that arises at PT Sinar Semesta is product quality that needs to be improved so that it can compete with other products on the market. Therefore to improve product quality, PT Sinar Semesta needs to be directly supported by all parties in the company and all operators, especially the production operators. This study used the Seven Tools Quality with the results of the research that in January - December 2021 PT Sinar Semesta produced 2091 Base Plate products, with a total of 301 defects. There were three types of defects studied in January - September 2021, namely perforated with 95 defects in Base Plate products, porous defects with 139 defects, and rough surface defects with 67 defects with a defect percentage of 31.56%, 46, 17%, and 22.26%.